Comparative Analysis of Oomycete Genome Evolution Using the Oomycete Gene Order Browser (OGOB). (11th December 2018) - McGowan, Jamie; Byrne, Kevin P; Fitzpatrick, David A
Abstract: The oomycetes are a class of microscopic, filamentous eukaryotes within the stramenopiles–alveolates–rhizaria eukaryotic supergroup. They include some of the most destructive pathogens of animals and plants, such as Phytophthora infestans, the causative agent of late potato blight. Despite the threat they pose to worldwide food security and natural ecosystems, there is a lack of tools and databases available to study oomycete genetics and evolution. To this end, we have developed the Oomycete Gene Order Browser (OGOB), a curated database that facilitates comparative genomic and syntenic analyses of oomycete species. OGOB incorporates genomic data for 20 oomycete species including functional annotations and a number of bioinformatics tools. OGOB hosts a robust set of orthologous oomycete genes for evolutionary analyses. Here, we present the structure and function of OGOB as well as a number of comparative genomic analyses we have performed to better understand oomycete genome evolution. We analyze the extent of oomycete gene duplication and identify tandem gene duplication as a driving force of the expansion of secreted oomycete genes. We identify core genes that are present and microsyntenically conserved (termed syntenologs) in oomycete lineages and identify the degree of microsynteny between each pair of the 20 species housed in OGOB. Consistent with previous comparative synteny analyses between a small number of oomycete species, our results reveal an extensive degree of microsyntenic conservation amongst genes with housekeeping functions within the oomycetes. OGOB is available at https://ogob.ie .